Microstrip Antenna Design for Femtocell Coverage Optimization - Afaz Uddin Ahmed; M. T. Islam; Rezaul Azim; Mahamod Ismail; Mohd Fais Mansor (International Journal of Antennas and Propagation)
A mircostrip antenna is designed for multielement antenna coverage optimization in femtocell network. Interference is the foremost concern for the cellular operator in vast commercial deployments of femtocell. Many techniques in physical, data link and network-layer are analysed and developed to settle down the interference issues. A multielement technique with self-configuration features is analyzed here for coverage optimization of femtocell. It also focuses on the execution of microstrip antenna for multielement configuration. The antenna is designed for LTE Band 7 by using standard FR4 dielectric substrate. The performance of the proposed antenna in the femtocell application is discussed along with results.